Determination of Nutritional Status of Northwest Anatolia (North Aegean) Olive Growing Areas - PEKCAN, Tülin; ÇOLAK ESETLİLİ, Bihter and TURAN, Hatice Sevim and AYDOĞDU, Erol (MAS Journal of Applied Sciences, 2022)
The study was carried out to determine the productivity of olive plantations in 8 different districts ofThe North Aegean Region. For this purpose, soil and leaf samples were taken simultaneously from 26 differentolive groves. 69.23% of the investigated surface soils (0-30 cm) are sandy loam, and 57.69% of the subsurfacesoils (30-60 cm) are sandy loam. It was determined that more than 50% of the soils were slightly alkaline andthe lime contents were low at both depths. It is seen that the organic matter contents of 11% of the surface soilsand 8% of the subsurface soils are low. Nitrogen contents at both depths are in the low class 38.46%. Theavailable phosphorus contents of 23.08% of the surface soils and 11.54% of the subsurface soils are sufficient.Available potassium and calcium contents in all surface soils are sufficient. It was determined that the potassiumcontent in 34.61% of the subsurface soils and the calcium content in 53.84% of the subsurface soils weresufficient and very high. It was determined that the available Mg content in 61.54% of the surface soil and 57.69%of the subsurface soil, was sufficient and very high. Sodium contents were determined adequately at both depths.When the leaf macro and secondary elements were examined according to the sufficiency limit values 46.15%of N, 26.92% of Ca 3.8% of Mg, and all the P and K contents, were found to be sufficient. of the microelements,42.31% of B, 76.92% of Fe, 46.15% of Mn and 38.46% of Zn are sufficient. Considering the results of the study,it is recommended to make fertilizer recommendation based on the results of soil and leaf analysis in parallelwith the regular cultural practices in order to obtain quality and high yield in North Aegean sustainable olivecultivation.